Picture of kid development with the stimulation playing Building Blocks In Kindergarten Al Ikhlas Perbon District Tuban - lukman hakim; mei widyawati (Jurnal Penelitian, 2019)
Phenomena that happen from 200 million kindergarten kids in a development country has failed reaching the potential optimal development because of poverty problem, malnutrition or an unsuitable environtment, until it demaged the cognitif development, motoric, emotion, and kids social. The purpose of this research is to know the picture of kids development with the stimulation of playing building blocks.The type of research is Deskristif with time Cross Sectional approach. The sample taking tehnique is using Total Sampling by 38 peoples. The data collection is using an observation sheet. The result of the research is it can be concluded the kids development with the behaviour aspect, partially good is 30 peoples  (78,9%), social emotion  and indepedently is 27 peoples (71,0%), language is 32 peoples (84,2%), motoric physique is 29 peoples (76,3%), art is 24 peoples (63,1%) and partially big cognitif aspect is 20 peoples (52,6%).It can be concludedthat there are a enough and good kids development, it’s recommended to the parents to know their kids development and the teacher to increase an educatif game.